Seasonally dry tropical forests ecology and conservation - Dirzo, Rodolfo; SpringerLink (Online service). (Washington, DC Island Press/Center for Resource Economics, 2011)
Though seasonally dry tropical forests are equally as important to global biodiversity as tropical rainforests, and are one of the most representative and highly endangered ecosystems in Latin America, knowledge about them remains limited because of the relative paucity of attention paid to them by scientists and researchers and a lack of published information on the subject.   Seasonally Dry Tropical Forests seeks to address this shortcoming by bringing together a range of experts in diverse fields including biology, ecology, biogeography, and biogeochemistry, to review, synthesize, and explain the current state of our collective knowledge on the ecology and conservation of seasonally dry tropical forests. The book offers a synthetic and cross-disciplinary review of recent work with an expansive scope, including sections on distribution, diversity, ecosystem function, and human impacts. Throughout, contributors emphasize conservation issues, particularly emerging threats and promising solutions, with key chapters on climate change, fragmentation, restoration, ecosystem services, and sustainable use. Seasonally dry tropical forests are extremely rich in biodiversity, and are seriously threatened. They represent scientific terrain that is poorly explored, and there is an urgent need for increased understanding of the system's basic ecology. Seasonally Dry Tropical Forests represents an important step in bringing together the most current scientific information about this vital ecosystem and disseminating it to the scientific and conservation communities.
Introduction -- PART I SEASONALLY DRY TROPICAL FORESTS AS A NATURAL SYSTEM. Chapter 1. Neotropical Seasonally Dry Forests: Diversity, Endemism, and Biogeography of Woody Plants -- Chapter 2. The Biogeography of Seasonally Dry Tropical Forests in South America -- Chapter 3. Extent and Drivers of Change of Neotropical Seasonally Dry Tropical Forests -- PART II ANIMAL BIODIVERSITY OF SEASONALLY DRY TROPICAL FORESTS. Chapter 4. Seasonally Dry Tropical Forest Soil Diversity and Functioning -- Chapter 5. Insect Diversity in Seasonally Dry Tropical Forests -- Chapter 6. Seasonally Dry Tropical Forest Mammals: Adaptations and Seasonal Patterns -- PART III ECOSYSTEM PROCESSES IN SEASONALLY DRY TROPICAL FORESTS. Chapter 7. Primary Productivity and Biogeochemistry of Seasonally Dry Tropical Forests -- Chapter 8. Physiological Mechanisms Underlying the Seasonality of Leaf Senescence and Renewal in Seasonally Dry Tropical Forest Trees -- Chapter 9. Water Dynamics at the Ecosystem Level in Seasonally Dry Tropical Forests -- PART IV HUMAN IMPACTS AND CONSERVATION IN SEASONALLY DRY TROPICAL FORESTS. Chapter 10. Impact of Anthropogenic Transformation of Seasonally Dry Tropical Forests on Ecosystem Biogeochemical Processes -- Chapter 11. Human Impacts on Pollination, Reproduction, and Breeding Systems in Tropical Forest Plants -- Chapter 12. Seasonally Dry Tropical Forest Biodiversity and Conservation Value in Agricultural Landscapes of Mesoamerica -- Chapter 13. Pasture Recolonization by a Tropical Oak and the Regeneration Ecology of Seasonally Dry Tropical Forests -- Chapter 14. Economic Botany and Management Potential of Neotropical Seasonally Dry Forests -- Chapter 15. Ecosystem Services in Seasonally Dry Tropical Forests -- Chapter 16. Climatic Change and Seasonally Dry Tropical Forests -- Chapter 17 Synthesis and Promising Lines of Research on Seasonally Dry Tropical Forests -- References -- Contributors -- Index.
Electronic reproduction.
Keywords: Forest ecology -- Tropics; Forest biodiversity -- Tropics; Forest conservation -- Tropics; Electronic books